Pengaruh Deskripsi Pekerjaan terhadap Kinerja Satpam PT Satria Sriwijaya Sejahtera - Sekar Ayu Ningtiyas; Badia Perizade; Wita Farla (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
This reseacrh aims to determine the effect of job descriptions on the performance of PT Satria Sriwijaya Sejahtera security guards. This study used quantitative methods with a questionnaire as a research instrument. The population in this study amounted to 35 people with 35 respondents. The sampling technique used is the census technique or total sampling. The data analysis technique used is simple linear regression. The findings of this research showed that there was a positive and significant effect between job descriptions on the performance of PT Satria Sriwijaya Sejahtera security guards. From the aspects that have been researched, it is better for the management of PT Satria Sriwijaya Sejahtera to explain more about SOPs and job descriptions of security guards to members of their security guards and pay more attention to aspects that can affect the performance of security guards so that the performance of security guards can increase. Keywords: Job Description, Employee Performance